Effect of laser power on microstructure and tensile properties of pulsed Nd:YAG laser beam welded AISI 301 austenitic stainless steel joints. (2021) - Gnanasekaran, S.; Senthil Kumar, S.; Venugopal, Narasimharaj; Upadhyaya, Makarand; Manjunath, T.C.; Chelladurai, Samson Jerold Samuel; Padmanaban, G.
Abstract: In this investigation, the effect of laser power on tensile properties and microstructure of AISI 301 austenitic stainless steel joints were studied. Five joints were fabricated using five different level of laser power varied between 350 W and 550 W respectively. The other parameters such as, welding speed, energy, focal position were kept constant. Of the five different laser power used, the joints fabricated using 550 W yielded superior tensile properties compared to other joints. Fine grain formation, negligible HAZ, prevention of sensitization and the presence of delta ferrite (δ) are the reasons for the superior tensile properties of these joints compared to other joints.